Budidaya Benih Lobster Pasir (Panulirus Homarus) Dengan Resirculation Aquaculture System (Ras) Di Pokdakan “Pesona Bahari”, Grand Watudodol, Banyuwangi - Attabik Mukhammad Amrillah; Mohamad Fadjar; Sri Andayani; Dwi Retno Andriani; I Gede Eko Putra Sri Sentanu; Attabik M. Amrillah; Diana Aisyah (Journal of Innovation and Applied Technology, 2022)
Puerulus or lobster seed (Panulirus homarus) often found in Banyuwangi teritory, in line with government regulations that prohibit to export lobster seeds, Lobster seed trading with seed size segmentation can be an alternative to improve the economy of people who are running the Covid19 pandemic. Seed size segmentation is needed because lobster cultivation as a consumption measure takes a long time. One of the efforts made in its cultivation in order to obtain growth rate and survival rate is Recirculation Aquaculture System (RAS). The aim of this activity is to produce “cricket” size seeds raised by RAS. Cultivation activities was carried out 2 months with different types of feed.  Parameters measured every two weeks are growth and survival rate. Water quality measured every day were temperature, DO, pH and salinity, while ammonia, nitrite, and nitrate were measured every two weeks. The results obtained was 100% survival rate.